Associations between digit ratio (2D4D), mood, and autonomic stress response in healthy men. (9th January 2019) - Walther, A.; Breidenstein, J.; Bösch, M.; Sefidan, S.; Ehlert, U.; Annen, H.; Wyss, T.; La Marca, R.
Abstract: The ratio between the length of the second (index) and the fourth (ring) finger (2D4D) is a putative biomarker of prenatal testosterone (T) exposure, with higher exposure leading to a smaller ratio. 2D4D has further been linked to mental and somatic disorders. Healthy male Swiss recruits ( N  = 245; Mage = 20.30 years) underwent a psychosocial stress test. Mood and salivary alpha‐amylase (sAA) were assessed before and after the stress test, while heart rate (HR) and heart rate variability (HRV) were measured continuously. Additionally, 2D4D (right: R2D4D; left: L2D4D) was determined and divided into quartile groups. Correlation analysis showed no associations between R/L2D4D and outcome measures. Comparing calculated quartiles for R2D4D, subjects in the lowest R2D4D quartile expressed trendwise ( p  < 0.10) lower positive and higher negative affect, significantly elevated sAA activity ( p  < 0.05), but no HR and HRV differences at baseline as compared to subjects in the upper three quartiles. With regard to acute stress, subjects in the lowest as compared to subjects in the upper three R2D4D quartiles showed a higher increase of negative affect and a stronger cardiac response ( p  < 0.05), but no alterations in positive affect and sAA activity. Young healthy men in the lowest R2D4D quartile revealed a more negative affect and increased physiological activity at baseline and in response to acute stress. An exposure to high levels of prenatal T might constitute a risk factor potentially increasing vulnerability to stress‐related disorders in men. Abstract : Although the role of the ratio between the length of the second (index) and the fourth (ring) finger (2D4D) as a putative biomarker for prenatal testosterone exposure is controversial, in the present study we found evidence that a lower right digit ratio (R2D4D) in males, reflecting higher prenatal testosterone levels is associated to worse mood and increased autonomic stress markers at baseline and in response to stress. An emerging model suggests that exposure to high levels of prenatal testosterone might constitute a risk factor potentially increasing vulnerability to stress‐related disorders in adult males.